HIGHER EDUCATION QUALITY IN THE CONTEXT OF THE SYNERGY OF SCIENTIFIC APPROACHES - Batechko, Nina (Continuing Professional Education: Theory and Practice, 2019)
The article considers the problem of the quality of higher education and its importance in the process of reforming the higher school of Ukraine. A definitive analysis of the concepts «quality», «quality of education», «quality of higher education» and differentiation of scientists’ thoughts on their interpretations has been made. The specified definitions are considered from the point of view of the system approach and it is established that «the quality of education» can be considered as a system object. The quality of education is also considered from the standpoint of the synergetic approach and it is proved that the object under study can be considered a synergistic category. It is proved that from the standpoint of systemic and synergetic approaches, the quality of education can be viewed as an open, non-linear system with integrated, interdisciplinary, purposeful, standardized and other aspects. In the context of general scientific approaches, the realities of the current state of introducing the principles of the quality of education in the higher school of Ukraine are considered. A comparison is made and the main differences in the formation of the Ukrainian and European systems for ensuring the quality of education are pointed out. It is pointed out that taking into account the best European practices in ensuring the quality of education and its own vision of the problem, taking into account the historical roots of the national education sphere, the Ukrainian mentality and its own scientific approaches will allow acceleration of the reform processes of the higher school of Ukraine and its European vector of development.